(untitled) (Economic and Political Thought, 2013)
Issues connected with competition policy are among the main aspects of ordoliberalism and a concept of social market economy. Unlike other neoliberals, ordoliberals expressed opinions that free competition, exempt from the control of the state, is a factor that endangers the free market economic system. The aim of the article is to carry out a comparative analysis of the contemporary Polish and German competition policies in the light of ordoliberalism and a concept of social market economy. The first part of the article is devoted to theoretical issues necessary to carry out a comparative analysis of competition policies in the two countries in the part of the work that follows.